2017
DOI: 10.1007/s10071-017-1138-y
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory behavior of a native anuran species with high invasive potential

Abstract: Exploratory behavior can be a key component of survival in novel or changing environments, ultimately determining population establishment. While many studies have investigated the behavior of wild animals in response to novel food items or objects, our understanding of how they explore novel environments is limited. Here, we examine how experience affects the foraging behavior of a species with high invasive potential. In particular, we investigate the movement and behavior of cane toads as a function of expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
3
1
Order By: Relevance
“…Thigmotaxis is commonly considered a measure of stress during captivity, hampering cognitive performance ( Harris et al 2009 ). Anxiety-related thigmotaxis usually decreases with increased familiarity with the experimental housing ( Simon et al 1994 ; Miller et al 2018 ), In contrast, we found weak differences in the proportion of time spent wall-following over the trials in G. quadricolor . Although thigmotaxis has not been validated as a boldness assay, it is reasonable to assume a positive relationship between open space use and boldness ( Carlson and Langkilde 2013 ), with thigmotactic individuals enhancing the probability of success in seeking shelters (e.g., Klosinki et al 2022 ), reducing at the same time the risk of being detected by natural enemies ( Harris et al 2009 ).…”
Section: Discussioncontrasting
confidence: 66%
“…Thigmotaxis is commonly considered a measure of stress during captivity, hampering cognitive performance ( Harris et al 2009 ). Anxiety-related thigmotaxis usually decreases with increased familiarity with the experimental housing ( Simon et al 1994 ; Miller et al 2018 ), In contrast, we found weak differences in the proportion of time spent wall-following over the trials in G. quadricolor . Although thigmotaxis has not been validated as a boldness assay, it is reasonable to assume a positive relationship between open space use and boldness ( Carlson and Langkilde 2013 ), with thigmotactic individuals enhancing the probability of success in seeking shelters (e.g., Klosinki et al 2022 ), reducing at the same time the risk of being detected by natural enemies ( Harris et al 2009 ).…”
Section: Discussioncontrasting
confidence: 66%
“…Thigmotaxis is commonly considered a measure of stress during captivity, hampering cognitive performance (Harris et al, 2009). Anxiety-related thigmotaxis usually decreases with increased familiarity with the experimental housing (Miller et al, 2018, Simon et al, 1994, as we observed in the native species. In contrast, we found weak differences in the proportion of time spent wall-following over the trials in G. quadricolor.…”
Section: δE Escape Frequencysupporting
confidence: 66%
“…The prolonged swimming could be related to the exploration and recognition of the new environment. Several studies have empirically demonstrated the importance of these behaviours in invasive species (Chapple et al, 2011; Chapple & Wong, 2016; Cote et al, 2010; Miller et al, 2018; Russell et al, 2010). Active exploration provides information about potential resources and risk factors and may be particularly beneficial when animals encounter novel environments.…”
Section: Discussionmentioning
confidence: 99%